1991
DOI: 10.1111/j.1365-2222.1991.tb01683.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and sensitization to dust mite allergens among asthmatic children in Sao Paulo, Brazil

Abstract: A group of 20 mite allergic asthmatic children aged 6-12 years old, living in São Paulo, Brazil, was studied regarding their degree of sensitization to house dust mites and exposure to mite allergens in their homes. In 18 out of 20 houses at least one dust sample was obtained which contained greater than 10 micrograms Der p I/g of dust. The highest levels of Dermatophagoides pteronyssinus allergens, Der p I and Group II, were measured in bedding samples (geometric mean 38.4 and 36.6 micrograms/g, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
13

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(98 citation statements)
references
References 28 publications
7
78
0
13
Order By: Relevance
“…It has been suggested that mechanical ventilation may have a major effect on indoor climate in cold regions but is unlikely to be effective in regions which have a humid outdoor climate for a significant part of the year (22,23). The finding that beds have higher Der p 1 levels than floors (12,24) and that bed, but not floor, levels arc associated with the severity of airway hyperresponsiveness (3) suggests that the microclimate that influences allergen exposure from beds may be more relevant to respiratory health than that which influences exposure from floors.…”
Section: Housing Characteristics Associated With House-dust Mite Prolmentioning
confidence: 74%
“…It has been suggested that mechanical ventilation may have a major effect on indoor climate in cold regions but is unlikely to be effective in regions which have a humid outdoor climate for a significant part of the year (22,23). The finding that beds have higher Der p 1 levels than floors (12,24) and that bed, but not floor, levels arc associated with the severity of airway hyperresponsiveness (3) suggests that the microclimate that influences allergen exposure from beds may be more relevant to respiratory health than that which influences exposure from floors.…”
Section: Housing Characteristics Associated With House-dust Mite Prolmentioning
confidence: 74%
“…Considerable research evidence suggests that both indoor and outdoor environmental exposures may be involved in the worldwide increase in asthma (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Some of the strongest associations have been found with indoor allergens such as dust mite and cockroach in children sensitized to that particular allergen (24)(25)(26)(27)(28)(29)(30)(31)(32). Exposure to environmental tobacco smoke, both in utero (15,19) and during childhood (17,18,20), also appears to play an important role in asthma causation and aggravation.…”
Section: Background On Asthma Prevalence Causation and Aggravationmentioning
confidence: 99%
“…The mite has been ubiquitously found in common houses in tropical and subtropical areas 1,2,7,10,21,23 . Although there have been a few reports indicating the scarce distribution of the genus Blomia in mainland of Japan 18,20 , the authors and other investigators have recently reported that B. tropicalis is one of the major mite species found in Okinawa, a subtropical prefecture of Japan 14,26,27 .…”
Section: Blomia Tropicalismentioning
confidence: 99%